“Downstreaming” Policy Supporting the Competitiveness of Indonesian Cocoa in the Global Market - Fahmid, Imam Mujahidin; Wahyudi,; Salman, Darmawan; Kariyasa, I Ketut; Fahmid, Mirah Midadan; Agustian, Adang; Perdana, Resty Puspa; Rachman, Benny; Darwis, Valeriana; Mardianto, Sudi (Frontiers in Sustainable Food Systems, 2022)
Indonesia is one of the cocoa producing countries, where most of it is exported to foreign countries and the rest is marketed domestically. Indonesia cocoa export performance in the world market certainly opens up many opportunities. It is necessary to optimize the potency and competitiveness of its cocoa if Indonesia would make the cocoa exports as the driving of national economy. The objectives of this paper are to (1) analyze Indonesian cocoa performance in the global market compared to its competitors and (2) analyze the competitiveness and market position of Indonesian cocoa in global market and analyze the potency to develop market in 10 main trading partners. The data analysis methods used are the Revealed Comparative Advantage (RCA), Trade Specialization Index (TSI) and Export Product Dynamics (EDP). The result shows that the comparative competitiveness of Indonesian cocoa beans and processed cocoa is lower than that of other producing countries. However, Indonesia still has the potency to develop market for its cocoa products in several countries such as the United States, China, India, Canada, Mexico and Estonia. Some efforts to improve the competitiveness of Indonesian cocoa beans may be through the replanting for estates rejuvenation and the improvement of fermentation to improve the quality of cocoa beans. In addition, to enhance the export performance of cocoa base products in general, it is necessary to also improve the development of downstream line and processing industries.